Clinic and Modern Endonasal Methods of Treatment of Chronic Etmoiditis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The latticed (Latin ethmoid) bone, also called the latticed labyrinth, got its name due to the fact that its complex structure is replete with through cells of different shapes and sizes. From the Latin name labyrinthus ethmoidalis, the diagnosis "ethmoiditis" is formed, meaning, again, inflammation of the mucous membrane of the ethmoid labyrinth. Like any other inflammatory process, ethmoiditis can occur in an acute or chronic type; like other sinusitis, it is more often detected in combination with inflammation of the adjacent paranasal sinuses (usually the maxillary sinuses of the upper jaw or the sphenoidal sinuses of the sphenoid bone located in the immediate vicinity – posteriorly from the ethmoid labyrinth). As a rule, treatment of chronic etmoiditis begins with conservative methods. After determining the drug sensitivity of the pathogen, etiotropic antibiotics or antimycotics, immunomodulators, anti-inflammatory drugs, vasodilators are prescribed (with great caution, since prolonged use can provoke an atrophic process in the mucous membranes), cuckoo washing and other measures according to indications. The article provides information on the clinical course of chronic etmoiditis, diagnosis and evaluation of the effectiveness эндоназальными of endonasal treatment.